Préparer l’entrée à l’école ? Analyse d’une pratique de transition œuvrant à la frontière entre l’école et les familles au sein d’un établissement scolaire du canton de Fribourg - Laurent Fahrni; Tania Ogay (Recherches en Éducation)
This article presents an analysis of a transition practice: a workshop aiming to help parents prepare their young children for school entry, taking place a few weeks before the beginning of the school year in a semi urban school in the canton of Fribourg, Switzerland. This is a particularly critical moment, since it is the first meeting between families and the school, during which mutual expectations crystallize, particularly in terms of preparation for school. Despite good intentions, this measure meant to facilitate school entry seems to miss its target, and even to be counter productive. The implicit and unspoken aspects of this pivotal moment are among the factors that explain this observation. We formulate reflective avenues for future editions but also, more generally, to promote a more egalitarian collaboration between families and schools.